Mid-infrared Nb₄N₃-based superconducting nanowire single photon detectors for wavelengths up to 10 μm - Yiming Pan; Hui Zhou; XINGYU ZHANG; Huiqin Yu; Lu Zhang; Mengting Si; Hao Li; Lixing YOU; Zhen Wang (Optica Publishing Group, 2022)
Mid-infrared (MIR) single-photon detection is emerging as an important technology for various applications. Superconducting nanowire single photon detectors (SNSPDs) fabricated with superconducting films with energy gaps of a few meV are natural broadband single-photon detectors. Recently, extending SNSPDs’ operation wavelengths into the MIR region is highly attractive. γ-Nb₄N₃ has a reduced N content and lower energy gap than the commonly used δ-NbN, making SNSPDs based on γ-Nb₄N₃ film more sensitive to low energy photons. We report on a Nb4N3-SNSPD based on 62-nm wide nanowire, with an optical absorption enhancement design and an optimized device package for efficient ZBLAN fiber coupling and dark count filtering. The developed device has a unity intrinsic detection efficiency (IDE) in the 1.5–4 μm wavelength region, and the device detection efficiency at 2.95 μm was measured to be 32.5%, with an uncertainty of 12.7%. Furthermore, we reduced the device geometry, and measured 3–10 μm photon response of a device based on 5-nm film and 42-nm nanowire, with an IDE of 95%, 81%, 40%, and 6% for 4.8, 6, 8, and 10 μm, respectively.
Keywords: Uncategorized